Problem-Based Learning: A Catalyst for the Development of Students' Critical Thinking and Science Process Skills - Bagus Cahyanto; Dhamas Mega Amarlita; Damajanti Kusuma Dewi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study investigates the implementation of a problem-based learning (PBL) model to enhance students’ critical thinking and science process skills in science courses. The research was conducted within the Islamic Elementary School Teacher Education Study Program, Faculty of Islamic Studies, University of Islam Malang. A qualitative approach was employed, utilizing interviews, observations, and documentation techniques for data collection. Data were analyzed through an interactive analysis model following the framework proposed by Miles, Huberman, and Saldana, consisting of three stages: data condensation, data display, and conclusion drawing/verification. The findings indicate that the Natural Science course was conducted through the application of the PBL model, which involved several key stages: (a) orienting students to the problem, (b) organizing students for learning, (c) guiding investigations, (d) developing and presenting solutions, and (e) analyzing and evaluating the problem-solving process. The application of the PBL model was found to significantly improve students’ critical thinking and science process skills. The results of this study are expected to provide valuable insights for lecturers and educational institutions in designing learning strategies that foster the development of students’ higher-order thinking and scientific inquiry skills. Further research is recommended to examine the long-term effects of the PBL model on students’ skill development and their preparedness for teaching practice.Keywords: natural science, critical thinking, science process skills, problem-based learning